2017
DOI: 10.3390/molecules22030388
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid as a Possible Pharmacological Source of Hydrogen Sulfide/Sulfane Sulfur

Abstract: The aim of the present study was to verify whether lipoic acid (LA) itself is a source of H2S and sulfane sulfur. It was investigated in vitro non-enzymatically and enzymatically (in the presence of rat tissue homogenate). The results indicate that both H2S and sulfane sulfur are formed from LA non-enzymatically in the presence of environmental light. These results suggest that H2S is the first product of non-enzymatic light-dependent decomposition of LA that is, probably, next oxidized to sulfane sulfur-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 40 publications
3
16
0
1
Order By: Relevance
“…These data may be due to the pharmadynamics and pharmakinetics properties of ALA which produces H2S in its catabolism. These data are in harmony with those obtained by Bilska-Wilkosz et al [50]. The last authors indicated that H2S is formed from ALA in the presence of environmental light.…”
Section: Table (3): Comparison Between Treatment By H 2 S Alone or Assupporting
confidence: 91%
“…These data may be due to the pharmadynamics and pharmakinetics properties of ALA which produces H2S in its catabolism. These data are in harmony with those obtained by Bilska-Wilkosz et al [50]. The last authors indicated that H2S is formed from ALA in the presence of environmental light.…”
Section: Table (3): Comparison Between Treatment By H 2 S Alone or Assupporting
confidence: 91%
“…It should be mentioned that 3-MP, in addition to acting as a substrate of 3-MST, can also produce H 2 S spontaneously (i.e., in solution, in the absence of any cellular components or enzymes) (Coletta et al, 2015). Moreover, lipoic acid, in addition to being a cofactor of the 3-MST reaction, has also been shown recently to release H 2 S nonenzymatically (Bilska-Wilkosz et al, 2017). These actions should be considered when interpreting the pharmacological effects of 3-MST, especially when substrates or cofactors are used at higher (micromolar) concentrations.…”
Section: A Brief Overview Of Endogenous H 2 S Sourcesmentioning
confidence: 99%
“…7 These compounds exhibit intriguing biological properties such as antimicrobial, antioxidant and anti-inflammatory. 2 [17][18][19][20] The metabolism of the drug has been widely studied both in experimental animals and humans as classical inductor of oxidative stress. 21,22 From the study, the group administered with SNP only showed significant increase in MDA concentration while rhodanese and GSH activity showed significant decrease compared to the control which may be attributed to the decomposition of SNP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nearly one billion of the world's population suffer from high blood pressure. [1][2] Sodium nitroprusside (SNP) is an antihypertensive agent used continuously in hypertensive emergencies. It decomposes into its metabolites that are pharmacologically inactive but induces toxicity within minutes of administration.…”
Section: Introductionmentioning
confidence: 99%